2015
DOI: 10.4012/dmj.2014-076
|View full text |Cite
|
Sign up to set email alerts
|

Influence of various superhydrophilic treatments of titanium on the initial attachment, proliferation, and differentiation of osteoblast-like cells

Abstract: The purpose of this study was to investigate the influence of superhydrophilic treatments of titanium on the behavior of osteoblastlike cells. Superhydrophilic specimens were prepared with sandblast and acid-etching (DW), oxygen plasma (Plasma) and ultraviolet light (UV), and were stored in distilled water for 3 days immediately after these treatments. Specimens stored in air for 3 weeks were used as a control Air group. Initial cell attachment, proliferation, alkaline phosphatase activity, and osteocalcin sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 32 publications
2
23
2
2
Order By: Relevance
“…The 0.6 nm surface roughness substrate exhibited higher hydrophilicity than the 1.7 nm surface roughness substrate. Although previous studies have reported that high hydrophilicity aids cell proliferation 11,12 , our results showed that the 1.7 nm surface roughness substrate that has lower hydrophilicity promoted higher cell proliferation than the 0.6 nm surface roughness substrate that has no grains. Undoubtedly, wettability is affected not only by surface roughness but also by the nanostructure.…”
Section: Discussioncontrasting
confidence: 97%
“…The 0.6 nm surface roughness substrate exhibited higher hydrophilicity than the 1.7 nm surface roughness substrate. Although previous studies have reported that high hydrophilicity aids cell proliferation 11,12 , our results showed that the 1.7 nm surface roughness substrate that has lower hydrophilicity promoted higher cell proliferation than the 0.6 nm surface roughness substrate that has no grains. Undoubtedly, wettability is affected not only by surface roughness but also by the nanostructure.…”
Section: Discussioncontrasting
confidence: 97%
“…As was seen by Yamamura et al 18 the surface of UV-treated implants demonstrated significant differences in chemical properties and wettability. Additionally, photofunctionalisation induced an accelerated increase in the BIC ratios in the early healing stage.…”
Section: Discussionmentioning
confidence: 66%
“…Sandblasted and acid-etched specimens (SB150E) of TZP were prepared by etched SB150 with 47% hydrofluoric acid (HF) for 15 min at room temperature 20) . SB150E of CpTi were prepared by etched SB150 with mixture of 36% hydrochloric acid (HCl) and 96% sulfuric acid (H 2SO4) for 3 min at 70°C 29) . Before use in cell culture experiments, all specimens were ultrasonically cleaned with acetone and distilled water for 10 min, followed by sterilization in an autoclave for 10 min at 121°C.…”
Section: Sample Preparationmentioning
confidence: 99%